Pharmacological inhibition of SK-channels with AP14145 prevents atrial arrhythmogenic changes in a porcine model for obstructive respiratory events. (19th May 2022) - Linz, B; Hesselkilde, EM; Skarsfeldt, MA; Hertel, JN; Sattler, SM; Yan, Y; Tfelt-Hansen, J; Diness, JG; Bentzen, BH; Linz, D; Jespersen, T
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): This work was supported by the Novo Nordisk Foundation (Tandem Programme; #31634). Background: Obstructive sleep apnea (OSA) creates a complex substrate for atrial fibrillation (AF), which is refractory to many clinically available pharmacological interventions. Purpose: To investigate atrial antiarrhythmogenic properties and ventricular electrophysiological safety of small-conductance Ca2+ -activated K+ (SK)- channel inhibition in a porcine model for obstructive respiratory events. Methods: In spontaneously breathing pigs, obstructive respiratory events were simulated by intermittent negative upper airway pressure (INAP) applied via a pressure device connected to the intubation tube. INAP was applied for 75 seconds, every 10 minutes, three times before and three times during infusion of the SK-channel inhibitor AP14145. Atrial effective refractory periods (AERP) were acquired before (Pre-INAP), during (INAP) and after (Post-) INAP. AF-inducibility was determined by a S1S2 atrial pacing protocol. For the purpose of drug safety, ventricular arrhythmicity was evaluated by heart rate adjusted QT-interval duration (QT-paced) and electromechanical window (EMW) calculation. Results: During vehicle infusion, INAP transiently shortened AERP (Pre-INAP: 135±10 ms vs. Post-INAP 101±11 ms; p=0.008) and increased AF-inducibility. QT-paced prolonged during INAP (Pre-INAP 270±7 ms vs. INAP 275±7 ms; p=0.04) and EMW shortened progressively throughout INAP and Post-INAP (Pre-INAP 80±4 ms; INAP 59±6 ms, Post-INAP 46±10 ms). AP14145 prolonged baseline AERP, partially prevented INAP-induced AERP-shortening and reduced AF-susceptibility. AP14145 did neither alter QT-paced (Pre-AP14145 270±7 ms vs. AP14145 268±6 ms, p=0.83) nor INAP-induced QT-paced prolongation, but blunted Post-INAP associated EMW-shortening. Conclusion: In a pig model for obstructive respiratory events, the SK-channel-inhibitor AP14145 prevented INAP-associated AERP-shortening and AF-susceptibility without impairing ventricular electrophysiology. Hence, SK-channels may represent a promising target for OSA-related AF.